A Meta-Analytic Review of Randomized Controlled Trials of the Good Behavior Game. Issue 4 (July 2021) - Smith, Stephanie; Barajas, Kimberly; Ellis, Brandi; Moore, Christina; McCauley, Spencer; Reichow, Brian
The Good Behavior Game (GBG) is widely recognized as an evidence-based intervention that reinforces prosocial behaviors and discourages disruptive behaviors among students in the classroom setting. The current meta-analysis synthesized randomized controlled trials of the GBG to examine its impact on proximal student outcomes across seven studies representing 4, 700 children. Although recent reviews focusing on single-case studies of the GBG have reported moderate to large treatment effects, our results were quite modest in comparison (hedges' g = 0.09-0.32). Treatment effect sizes also varied according to outcome and sex. The GBG significantly outperformed the comparison conditions for peer-rated conduct problems and shy/withdrawn behavior as well as teacher-rated conduct problems for which a greater effect was found for girls relative to boys. Moreover, the treatment effect in favor of the GBG for reading comprehension was specific to boys and not girls. No significant differences were found between the GBG and comparison conditions for inattention and teacher-rated shy/withdrawn behavior. These results suggest that the GBG may not be as impactful as originally reported and the intended population and treatment targets should be considered before its implementation in the classroom.